Ayat jamilah = Beautiful signs : a treasury of Islamic wisdom for children and parents - Conover, Sarah (This little light of mine series, 2004)
Presents a collection of Islamic verse, folk tales, and figures from the Qur'an and the traditions around the Muslim world and also includes detailed explanatory notes.